Cash transfer programs with income multipliers: PROCAMPO in Mexico - Sadoulet, Elisabeth; Davis, Benjamin; De Janvry, Alain (International Food Policy Research Institute, 2001)
Cash transfer programs induce multiplier effects when recipients put the money they receive to work to generate additional income. The ultimate income effects are multiples of the amounts transferred. This paper analyzes the PROCAMPO program in Mexico, which was introduced to compensate farmers for the anticipated negative effect of the North American Free Trade Agreement (NAFTA) on the price of basic crops. The transfer rules and the timing of the panel data collected allow unique control of biases in this impact analysis. We find that the multiplier among ejido sector recipients is in the range of 1.5 to 2.6. Multipliers are higher for medium and large farm households, low numbers of adults in the household, nonindigenous backgrounds, and households located in the Center and Gulf regions. High multipliers reflect marginal income opportunities that were unrealized due to liquidity constraints that the transfers eased. Opportunities came from the asset endowments that these households have, particularly irrigated land, and these opportunities were enhanced by access to technical assistance.